Un estudio de la palabra QUE en canciones hispanas - Corrales-Martín, Norma (2006)
This article describes a paradigm of uses of the word que, one of the most peripatetic words in Spanish. For our analysis we chose 37 popular Caribbean songs due to the richness and variety of Spanish reflected in these songs